Prova de absorção de gordura em crianças. - Moreira, F. L.; Maffei, H. V.; Padovani, C. R.; Campana, A. O. (My University, 1987)
To overcome the difficulties observed with fecal fat estimations, we studied fat absorption in 4 m to 12 years old children, assessing increments of serum triglycerides after administration of corn oil. Eighteen well-nourished children without gastrointestinal symptoms or parasites, 31 children with protein-calorie malnutrition (PCM), with or without protracted diarrhea and/or intestinal parasites and nine children with specific malabsorptive entities were studied. Serum triglycerides (TG) were measured before, 2 and 4 hours after the administration of 2 g/kg of corn oil per os. For control infants below 2 years no significant differences between the fasting level and those after 2 and 4 hours were observed. For children above this age significant absorption occurred by 2 hours but more intensively after 4 hours, an increment of TG above 35 mg% being considered normal. A good discrimination between TG increments of controls and malabsorptive children over 2 years was observed. In conclusion, the oral fat loading test, is applicable for children over 2 year of age. For infants below this age other schedules should be tested.
The fat absorption test in children
Keywords: corn oil; diagnostic agent; fatty acid; triacylglycerol; blood; child; human; infant; intestine absorption; malabsorption; metabolism; preschool child; protein calorie malnutrition; Child; Child, Preschool; Corn Oil; English Abstract; Fatty Acids; Human; Infant; Intestinal Absorption; Malabsorption Syndromes; Protein-Energy Malnutrition; Triglycerides